Najemna pogodba med gospodarskimi subjekti v obliki neposredno izvršljivega notarskega zapisa - Feguš, Primož (Podjetje in delo, 2014)
One of the legal instruments for securing liquidity operations is the immediately enforceable notarial act. The author discusses its various advantages, focusing on the ability to obtain the possession of leased premises when a tenant has defaulted on his rental payments. In recent years, lessors have faced increasing difficulties due to the non-payment of rent obligations. Rental income derived from the leasing of commercial properties typically represents an important source of revenue for lessors. The author believes that presentation of an immediately enforceable notarial act can also be used at the conclusion of the lease contract, in order to protect the lessor against the debtor tenant. A lease contract in the form of the immediately enforceable notarial act allows the lessor to immediately start the lease termination process when the tenant breaches the rental agreement or the Office Buildings and Business Premises Act. The immediate enforceable notarial act is the legal title, allowing the court to start the execution process immediately upon the receipt of the request for enforcement, which may not be suspended by the debtor's objection. Lessors need to be aware of the various advantages of the immediately enforceable notarial act when seeking to terminate the lease contract for the lessee's failure to pay. In selecting a lease contract in form of the immediately enforceable notarial act, lessees have fewer options upon their breach of the lease agreement. If lessors choose to incorporate the notarial act in their lease contracts as common practice, lessees will have fewer options upon their breach of the lease contract. As a result, the immediately enforceable notarial act could potentially lead to the common conclusion that indebtedness is not acceptable and should be reduced in the future.
Keywords: najem; notarji; pogodbe; poslovni prostori